A Novel in‐Frame 18‐bp Microdeletion in MT‐CYB Causes a Multisystem Disorder with Prominent Exercise Intolerance. Issue 8 (28th June 2014) - Carossa, Valeria; Ghelli, Anna; Tropeano, Concetta Valentina; Valentino, Maria Lucia; Iommarini, Luisa; Maresca, Alessandra; Caporali, Leonardo; La Morgia, Chiara; Liguori, Rocco; Barboni, Piero; Carbonelli, Michele; Rizzo, Giovanni; et al.
<x xml:space="preserve">Abstract</x> This study shows that a complex multisystem disorder with prominent exercise intolerance is associated with an 18‐bp mtDNA deletion in the MT‐CYB gene (m.15649_15666del18). This rearrangement, which involves two identical six bp direct repeats located 12‐bp apart from each other, causes the loss of six amino acids in the protein, but leaves the remaining of the MT‐CYB sequence in frame. Cybrid studies revealed that the defective complex III function was cotransferred with mutant mtDNA, thus unequivocally establishing the pathogenic role of the deletion. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>